2019
DOI: 10.1080/17405904.2019.1573148
|View full text |Cite
|
Sign up to set email alerts
|

‘Piketty is a genius, but … ’: an analysis of journalistic delegitimation of Thomas Piketty’s economic policy proposals

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles 'Piketty is a genius, but … ': an analysis of journalistic delegitimation of Thomas Piketty's economic policy proposals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The number of survey respondents was quite small, and a more comprehensive empirical study would surely benefit scholarship on journalism practice and economic expertise. Moreover, this article sidelined influential international economic institutions, like the European Central Bank (ECB) and the International Monetary Fund (IMF), not to mention such globally prominent superstar economists as Thomas Piketty, whose arguments are debated in the public sphere (see Rieder and Theine 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The number of survey respondents was quite small, and a more comprehensive empirical study would surely benefit scholarship on journalism practice and economic expertise. Moreover, this article sidelined influential international economic institutions, like the European Central Bank (ECB) and the International Monetary Fund (IMF), not to mention such globally prominent superstar economists as Thomas Piketty, whose arguments are debated in the public sphere (see Rieder and Theine 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We find that two competing frames (DiMaggio et al, 2013 )—an economic efficiency frame and a social justice frame—variously imbue the wealth tax with meaning. While prior research finds that in public discourse on the taxation of wealth, purported negative economic implications are often invoked to underline opposition to this measure (Leipold, 2019 ; Lichtenstein et al, 2016 ; Rieder & Theine, 2019 ), we need more systematic evidence for how arguments that are crafted in the political sphere might resonate with a broader public. Our findings suggest that evocative language and political symbolism may play a crucial role in this regard: in the parliamentary debates we analyse, Conservatives’ use of the efficiency frame often rests on biological metaphors.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Lichtenstein et al ( 2016 ) study media representations in 2013, an election year, and find that worries about negative economic consequences of the wealth tax are a dominant theme across different types of media outlets, over and above favourable arguments around its redistributive effects, considerations about how the revenue could be used, and legal issues concerning its feasibility as well as its implementation. Rieder and Theine ( 2019 ) investigate how the policy proposals put forward by French economist Piketty are portrayed in the media in Germany and four additional European countries in 2014 and 2015. Focusing on counter-arguments to Piketty’s suggestions, the authors find a set of highly symbolically charged arguments that focus on negative economic consequences of taxing wealth as well as on discursive strategies such as portraying “the rich and entrepreneurs as victims lacking agency in the face of an aggressive, overpowering and abusive state” (ibid.…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the issue of income inequality and poverty has shown a high degree of correlation and a long-term major problem for all countries of the world (Milanović, 2015). Critical review of Piketty's work was about what to do against the rise of economic inequality which is highly controversy and about agreement with Piketty's policy proposals such as higher taxation on income, wealth and inheritances dropped significantly (Rieder & Theine, 2019).…”
Section: Literary Reviewmentioning
confidence: 99%